A49 PRECLINICAL STUDIES OF TWO NOVEL LIVE BIOTHERAPEUTIC PRODUCTS FOR THE TREATMENT OF ULCERATIVE COLITIS. (21st February 2022) - Verdugo Meza, A; Ye, J; Gill, S K; Barnett, J A; Haskey, N; Gibson, D L
Abstract: Background: The therapeutic approaches for ulcerative colitis present a high failure rate. Therefore, more therapeutic options are in the spotlight. Live biotherapeutic products, a more rationalized and tailored approach than probiotics, have a broader effect since they are not limited to a single therapeutic target. Aims: To characterize the therapeutic effect of BioColoniz and BioPersist, two live biotherapeutic products derived from Lactobacillus reuteri and E. coli Nissle 1917, respectively, in rodent models of colitis. Methods: To test the therapeutic effect of BioColoniz, 5 weeks old Muc2 -/- mice, which spontaneously develop colitis, received a single dose of BioColoniz, L. reuteri or Vehicle via oral gavage; mice were monitored weekly until they showed clinical signs of disease and were euthanized. To evaluate the therapeutic effect of BioPersist, 6 weeks old C57BL/6 mice received BioPersist or vehicle via oral gavage, and then were exposed for 7 days to DSS for induction of acute colitis; parallel, mice received 5-ASA or vehicle daily. For both experiments, colons were collected and evaluated for macroscopic and histopathological changes. Results: Mice treated with BioColoniz presented lower clinical scores, with a greater weight gain when compared to mice treated with L. retueri or vehicle. The appearance of rectal prolapse, a hallmark of the Muc2 -/- model, was only recorded in mice treated with L. reuteri or Vehicle, supporting the protective effect of BioColoniz in the Muc2 -/- model. Although the macroscopic analysis showed no changes in colon length among the groups, the histopathological analysis revealed decreased damage in mice treated with BioColoniz, significant when compared to mice who only received the vehicle. In order to evaluate if BioColoniz also protects against the development of comorbid metabolic defects of colitis, mice were also subjected to oral glucose tolerance test, finding that BioColoniz treated mice, especially males, display an improved glucose clearance when compared to L. retueri or vehicle groups. In the DSS model, BioPersist decreased daily clinical scores, significantly delaying the weight loss. The macroscopic analysis showed greater colon length in BioPersist treated mice than in mice treated only with 5-ASA, along with decreased histopathological damage. Conclusions: Altogether, BioColoniz and BioPersist reduce the colitic phenotype in the Muc2 -/- and DSS colitis models, respectively. Furthermore, BioColoniz protects Muc2-/- mice from the metabolic detriments of colitis. Future studies will focus on describing the mechanisms by which BioColoniz and BioPersist confer their therapeutic effect. Funding Agencies: CCCMSFHR